Comparison of Insulin Aspart vs. Regular Human Insulin with or without Insulin Detemir Concerning Adipozytokines and Metabolic Effects in Patients with Type 2 Diabetes Mellitus - Herrmann, B. L.; Kasser, C.; Keuthage, W.; Huptas, M.; Dette, H.; Klute, A. (Experimental and Clinical Endocrinology & Diabetes, 2013)
In type 2 diabetes mellitus, treatment with insulin is initiated when HbA1c is reduced inadequately with oral antidiabetic drugs or incretin mimetics. Whether insulin analogues vs. regular human insulin have favorable effects in terms of efficacy and metabolism is under discussion.29 patients with type 2 diabetes mellitus (19 males, 10 females) with a mean age 59±11(mean±SD) years (range 24–75) and treated with oral drugs for at least 6 months and a HbA1c >7.0% were included in an open, randomised, prospective, controlled, multicenter parallel-group study over a period of 24 months.11 patients were randomized in the regular human insulin-group (RHI-group) and 18 patients in the insulin aspart group (IA-group). Insulin aspart or regular human insulin should be treated to <140 mg/dl postprandial and insulin detemir should be treated to <110 mg/dl in the morning (fasting) after a previous dose titration of insulin aspart or regular human insulin over 6 months of treatment. Adiponectin, HbA1c, fasting plasma glucose, BMI, triglycerides and cholesterol levels were determined every 3 months.7/11 of the RHI-group received additional insulin detemir and 13/18 of the IA-group. HbA1c levels decreased significantly in both groups (8.7±1.6 to 7.2±0.9 in the RHI-group (p<0.05) vs. 8.7±1.6 to7.3±0.9 in the IA-group (p<0.05)) without significant difference between the groups. No significant changes were seen between the 2 groups during the 24 months period in terms of BMI, fasting plasma glucose, lipids. Adiponectin serum levels decreased over the time without difference between the groups (7.9±4.0 to 5.0±2.0 in the RHI-group (p<0.03) vs. 7.3±3.4 to 4.8±2.8 in the IA-group (p<0.0001)). During the first 9 months, the insulin dosage to reach the postprandial blood glucose <140 mg/dl, were significantly lower in the IA-group, but approached the following the RHI-group without significant changes after 24 months.After stopping oral antidiabetic drugs in type 2 diabetes mellitus, insulin aspart in comparison to human regular insulin decreased effectively HbA1c levels without significant difference. Moreover, insulin aspart in comparison to human regular insulin does not have any substantial benefits concerning metabolic effects and adipocytokines in type 2 diabetes mellitus over a 24 months treatment period.
Keywords: adipocytokines; insulin; type 2 diabetes mellitus